Education of musical culture of pupils in a context of humanistic pedagogics - Rakitjanska, L.M. (Pedagogy of Higher and Secondary Education, 2007)
Modern approaches to the aims of musical education that are conceptually important in terms of humanistically oriented pedagogics are regarded in the article.